Chapter The North-east Atlantic Margin - Morrissey, Declan (Taylor & Francis, 2023)
The Irish-Scottish margin is geologically and oceanographically heterogeneous. Source waters of subpolar and subtropical origin interact with banks, seamounts, submarine canyon systems, escarpments, and mound provinces resulting in rich and diverse benthic communities that are influenced by local and regional hydrodynamics (e.g., internal waves, tides, and local turbulence). Reef habitats formed by the cold-water coral Desmophyllum pertusum are particularly well studied, such that controls on reef and mound formation are relatively well understood. The distribution of some other Vulnerable Marine Ecosystems (VMEs), such as sponge fields formed by Pheronema carpenteri, and xenophyophore aggregations, is known due to both field observations and predictive modelling. Some VMEs are poorly known, for example, coral gardens, where in many cases even the characteristic species are not fully identified. The autecology of some component species has been studied, but for others, knowledge is almost completely lacking. The evidence for increased biodiversity associated with all these habitats is clear and all suffer anthropogenic impacts.